A Hybrid PI–SOSM Control Strategy with Disturbance Observer for Enhanced Dynamic Response of IM Drives - Pham, Thanh Tinh; Pham, Ngoc Thuy (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
This paper proposes a novel hybrid field-oriented control (FOC) strategy for high-performance induction motor (IM) drives, integrating a conventional Proportional–Integral (PI) controller in the speed loop and a Super-Twisting Second-Order Sliding Mode (SOSM) controller in the current loop. The main novelty lies in combining a sliding mode disturbance observer (OB) with a hybrid PI–SOSM structure, enabling real-time estimation and compensation of unknown load torque. The estimated torque is transformed into an equivalent disturbance current, which is directly added to the torque-producing current reference, thereby achieving feedforward disturbance rejection. The novel hybrid structure achives the improved dynamic response and robustness through self-compensated torque disturbance using OB, reduced chattering in current regulation via SOSM, and maintaining PI simplicity in the outer speed loop. Extensive simulation results by MATLAB/Simulink sotfware demonstrates that the hybrid controller offers superior dynamic performance, enhanced robustness against parameter uncertainties and load disturbances, and significantly reduced chattering effects compared with conventional PI–PI FOC.